The poetics of grammar and the metaphysics of sound and sign - La Porta, S.; Shulman, David Dean, 1949- (Jerusalem Studies in Religion and Culture, 2007)
This book examines the seemingly universal notion of a grammatical cosmos. Individual essays discuss how many of the great civilizations provide cognitive maps that emerge from a metaphysical linguistics in which sounds, syllables and other signs form the constructive elements of reality. The essays address cross-cultural issues such as: Why does grammar serve as a template in these cultures? How are such templates culturally contoured? To what end are they applied - id est, what can one do with grammar - , and how does it work upon the world? The book is divided into three sections that deal with the metaphysics of linguistic creation; practices of encoding and decoding as a means of deciphering reality; and language in the widest sense as a medium for self- and cultural transformation. Contributors include: Jan Assman, Sara Sviri, Michael Stone, M. Finkelberg, Yigal Bronner, Martin Kern, Brouria Bitton-Ashkelony, Dan Martin, Jonathan Garb, Tom Hunter, David Shulman, and Sergio La Porta.